Krüppel-like factor 6 interferes with cellular transformation induced by the H-ras oncogene - Trucco, Lucas Daniel (2014)
KLF6 is a member of the Krüppel-like factor family of transcription factors, with diverse roles in the regulation of cell physiology, including proliferation, signal transduction, and apoptosis. Mutations or down-regulation of KLF6 have been described in several human cancers. In this work, we found that KLF6-knockdown resulted in the formation of transformed foci and allowed the spontaneous conversion of NIH3T3 cells to a tumorigenic state. We further assessed the role of KLF6 in the context of oncogenic Ras. We showed that KLF6 was up-regulated by H-RasG12V expression in a Jun N-terminal kinase (JNK)-dependent manner, correlated with enhanced klf6 promoter activity. We found that ectopic KLF6 expression induced a G1-phase cell cycle arrest, thereby decreasing the cell proliferation rate. In addition, constitutive KLF6 expression impaired H-RasG12V-mediated loss of density-dependent growth inhibition and anchorage-independent growth. Moreover, growth of H-RasG12V-driven tumors was reduced in mice challenged with cells stably expressing KLF6. KLF6 expression correlated with the up-regulation of p21, whereas neither p53 induction nor apoptotic cell death was detected. Further, p21 knockdown impaired KLF6-induced cell cycle arrest. These findings provide novel evidence highlighting KLF6 function in response to malignant transformation, suggesting the relevance of KLF6 in controlling cell proliferation and hindering tumorigenesis.